The identification of a mutant peptide of an abnormal haemoglobin by mass spectrometry - Morris,HR; Williams,DH (Journal of the Chemical Society Chemical Communications, 1972)
A mutant peptide from an abnormal haemoglobin, contaminated by a second peptide, has been sequenced by mass spectrometry; the spectrum of one derivatised mixture allowed the sequences Leu-Leu-Gly-Asn-Val-Leu-Phe and Leu-Leu-Val-Val-Tyr-Pro-Trp to be determined.